MASSIVE PLEURAL EFFUSION: A CASE REPORT - Tresna Dewi, Putu Bayu Dian (E-Jurnal Medika Udayana; vol 2 no3 (2013):e-jurnal medika udayana, 2013)
Pleural effusion is abnormal fluid accumulation within pleural cavity between the parietal pleura and visceralis pleura, either transudation or exudates. A 47 year-old female presented with dyspneu, cough, and decreased of appetite. She had history of right lung tumor. Physical examination revealed asymmetric chest movement where right part of lung was lagged during breathing, vocal fremitus on the right chest was decreased, dullness at the right chest, decreased vesicular sound in the right chest, enlargement of supraclavicular and colli dextra lymph nodes, and hepatomegali. Complete blood count showed leukocytosis. Clinical chemistry analysis showed hipoalbumin and decreased liver function. Blood gas analysis showed hypoxemia. Pleural fluid analysis showed an exudates, murky red liquid color filled with erythrocytes, number of cells. Cytological examination showed existence of a non-small cell carcinoma tends adeno type. From chest X-ray showed massive right pleural effusion. Based on history, physical examination and investigations, she was diagnosed with massive pleural effusion et causa suspected malignancy. She had underwent pleural fluid evacuation and treated with analgesics and antibiotics.
Keywords: pleural effusion, malignancy, dyspneu